MORE THAN CONVENIENCE: SOCIAL INFLUENCE SHAPES THE PATH FROM PERCEIVED USEFULNESS TO ACTUAL E-WALLET USE - Haryanto, Hery; Tu, Michelle Nataline; Hesniati (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2026)
Purpose - This study extends the Technology Acceptance Model to explain Indonesian e-wallet continuance by examining perceived usefulness, perceived ease of use, gamification effectiveness, trust in provider, loyalty program intensity, social influence, intention to continue use, and actual usage frequency. Methods – A quantitative survey of 290 Indonesian e-wallet users was analyzed using partial least squares structural equation modeling. Findings – The findings show that perceived usefulness, perceived ease of use, gamification, trust, and loyalty programs have a positive effect on intention to continue use. Intention to continue use also has a significant effect on actual usage frequency. Social influence strengthens the association between perceived usefulness and the intention to continue using it but does not significantly moderate perceived ease of use. Research Implications – The study adds to the body of knowledge on post-adoption behavior for sustainable digital payment usage and to strengthening the cashless payment ecosystem in Indonesia. Originality – This research extends the Technology Acceptance Model by incorporating actual usage frequency as the final behavioral outcome in Indonesian e-wallet users.